2012
DOI: 10.1189/jlb.1011500
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived, tolerogenic dendritic cells suppress immune rejection in the indirect allosensitization-dominant setting of corneal transplantation

Abstract: Significant interest has been focused on the use of ex vivo-manipulated DCs to optimally induce transplant tolerance and promote allograft survival. Although it is understood that donor-derived, tolerogenic DCs suppress the direct pathway of allosensitization, whether such DCs can similarly suppress the indirect pathway remains unclear. We therefore used the murine model of corneal transplantation to address this, as these allografts are rejected in an indirect pathway-dominant manner. Interestingly, recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 38 publications
3
46
0
1
Order By: Relevance
“…One possible explanation for this reduced immune response could be provided by the finding that lymph nodes from sCD83-treated mice contained significantly higher levels of CD4 + Foxp3 + T cells. It has been shown recently that the frequency of Foxp3 + T cells is crucial for the induction of tolerance in corneal transplantation (53,54). In line with the restimulation results, more CD4 + Foxp3 + T cells could not be observed in the spleen, indicating again that immune modulation by the topical application of sCD83 is local and possible side effects might be reduced.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…One possible explanation for this reduced immune response could be provided by the finding that lymph nodes from sCD83-treated mice contained significantly higher levels of CD4 + Foxp3 + T cells. It has been shown recently that the frequency of Foxp3 + T cells is crucial for the induction of tolerance in corneal transplantation (53,54). In line with the restimulation results, more CD4 + Foxp3 + T cells could not be observed in the spleen, indicating again that immune modulation by the topical application of sCD83 is local and possible side effects might be reduced.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, we wanted to determine whether sCD83 application at the graft-host interface (i.e., topically) also induces IDO-mediated immune regulatory effects. Because of the molecule size of 16.7 kDa, sCD83 is able to penetrate the corneal stroma and is therefore suitable for topical treatment, because it has been shown that molecules up to 56 kDa can penetrate a healthy cornea and that larger molecules (up to 149 kDa) can be used to penetrate the inflamed cornea (52,53). The great advantage of topical drug administration to the cornea is 1) easy deposition of the drug by the patient himself, 2) the reduction of drug concentration, and 3) reduction of possible side effects, which can occur via systemic application.…”
Section: Discussionmentioning
confidence: 99%
“…5 Regulatory T cells (Tregs) and maturation-resistant tolerogenic dendritic cells (tolDCs) have been used in experimental models to induce tolerance and thus eliminate the use of immunosuppressive agents. 61,63,104 It has been shown that in vitro expansion of Tregs can also significantly promote allograft survival. 76 Our recent study demonstrated that systemic administration of low-dose IL-2 expands Tregs in vivo, enhances their function, and ultimately promotes graft survival.…”
Section: Novel Strategies For Immunomodulation In Corneal Transplamentioning
confidence: 99%
“…Penetrating keratoplasty was performed as described previously [19, 20]. Briefly, the central cornea (2 mm in diameter) was excised from a donor C57BL/6 mouse (2 mm bore trephine) using curved Vannas scissors (Storz Instruments, San Dimas, CA, USA) and placed on ice in phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%